Relationship between primary school healthy eating and physical activity promoting environments and children's dietary intake, physical activity and weight status: a longitudinal study in the West Midlands, UK. Issue 12 (22nd December 2020) - Garden, Elizabeth Mairenn; Pallan, Miranda; Clarke, Joanne; Griffin, Tania; Hurley, Kiya; Lancashire, Emma; Sitch, Alice J; Passmore, Sandra; Adab, Peymane
Abstract : Objective: We aimed to examine the association between food and physical activity environments in primary schools and child anthropometric, healthy eating and physical activity measures. Design: Observational longitudinal study using data from a childhood obesity prevention trial. Setting: State primary schools in the West Midlands region, UK. Participants: 1392 pupils who participated in the WAVES (West Midlands ActiVe lifestyle and healthy Eating in School children) childhood obesity prevention trial (2011–2015). Primary and secondary outcome measures: School environment (exposure) was categorised according to questionnaire responses indicating their support for healthy eating and/or physical activity. Child outcome measures, undertaken at three time points (ages 5–6, 7–8 and 8–9 years), included body mass index z-scores, dietary intake (using a 24-hour food ticklist) and physical activity (using an Actiheart monitor over 5 days). Associations between school food and physical activity environment categories and outcomes were explored through multilevel models. Results: Data were available for 1304 children (94% of the study sample). At age 8–9 years, children in 10 schools with healthy eating and physical activity-supportive environments had a higher physical activity energy expenditure than those in 22 schools with less supportive healthy eating/physical activity environments (mean difference=5.3 kJ/kg body weight/24 hours; p=0.05). Children in schools with supportive physical activity environments (n=8) had a lower body mass index z-score than those in schools with less supportive healthy eating/physical activity environments (n=22; mean difference=−0.17, p=0.02). School food and physical activity promoting environments were not significantly associated with dietary outcomes. Conclusions: School environments that support healthy food and physical activity behaviours may positively influence physical activity and childhood obesity. Trial registration number: ISRCTN97000586 .